The incredible journey of plants eaudiobook - Mancuso, Stefano (Tantor Media, 2020)
When we talk about migrations, we should study plants to understand that these phenomena are unstoppable. In the many different ways plants move, we can see the incessant action and drive to spread life that has led plants to colonize every possible environment on earth. The history of this relentless expansion is unknown to most people, but we can begin our exploration with these surprising tales, engagingly told by Stefano Mancuso. Generation after generation, using spores, seeds, or any other means available, plants move in the world to conquer new spaces. The number and variety of tools through which seeds spread is astonishing: we have seeds dispersed by wind, by rolling on the ground, by animals, by water, or by a simple fall from the plant, which can happen thanks to propulsive mechanisms, the swaying of the mother plant, the drying of the fruit, and much more. In this accessible, absorbing overview, Mancuso considers how plants convince animals to transport them around the world, and how some plants need particular animals to spread; how they have been able to grow in places so inaccessible and inhospitable as to remain isolated; how they resisted the atomic bomb and the Chernobyl disaster; how they are able to bring life to sterile islands; how they can travel through the ages, as they sail around the world.